Analysis Of Student Errors in Solving Story Problems Based on New Procedures in Terms of Mathematical Problem-Solving Skills - Itqan, Moh Syadidul; Monica, Sandra Yayang; Afcarina, Nor Izza (Lembaga Riset Mutiara Akbar, 2022)
Class XI students often make mistakes when working on problem solving problems in the form of story questions. One way that can be used to find out the cause of this happening is to analyze student errors in solving mathematical problem solving. This study aims to determine the type of error and the percentage of error solving problems based on the Newman procedure. This research was conducted at MAN 1 Probolinggo in the academic year 2021/2022. This type of research is qualitative research. Data was collected using tests and interviews. The research subjects in this study were students of class XI IPA, totaling 30 students. Interview subjects were taken by purposive sampling. The research subjects to be interviewed were taken from 6 of 30 students of class XI science, each consisting of 3 students from the upper group, the middle group and the lower group. Each research subject was interviewed related to the results of his work on the story problems of social Arithmetic material. The test used in this study was 4 problem solving essay questions. The data analysis used includes data reduction, data presentation, and verification. The results of this research are expected to provide suggestion on the application of learning methods, after knowing the students' mathematical problem solving errors.